2021
DOI: 10.1021/acsanm.1c01714
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Mediated Growth of Pt on High-Index Faceted Au Nanocrystals: The Ag Lining and Implications for Electrocatalysis

Abstract: Bimetallic Au@Pt nanocrystals (NCs) offer a unique combination of plasmonic and catalytic properties and are a growing field of research. Herein, we report an unusual observation in the behavior of silver ions (Ag + ), which was found to play a dominant role in dictating the Pt deposition in a seed-mediated growth method. While the literature is replete with various instances of Ag-assisted Pt deposition whereby higher concentration of Ag + translates into a thicker Pt shell, in the present study, contradictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This method allows for the full integration of MOF advantages, leading to substantial synergistic effects. [149][150][151] Huang et al have devised a seed-mediated growth method approach to create CoFe 2 O 4 @CuO microcages originating from core-shell dual-MOF heterostructures (Fig. 5A and B).…”
Section: Multi-step Seed-mediated Growth Methodsmentioning
confidence: 99%
“…This method allows for the full integration of MOF advantages, leading to substantial synergistic effects. [149][150][151] Huang et al have devised a seed-mediated growth method approach to create CoFe 2 O 4 @CuO microcages originating from core-shell dual-MOF heterostructures (Fig. 5A and B).…”
Section: Multi-step Seed-mediated Growth Methodsmentioning
confidence: 99%
“…This can be explained due to a lattice mismatch between Pt and Au and the strong Pt-Pt bonds. Roy et al (2021) achieved the smooth coverage of Pt whilst maintaining the seed morphology through the addition of Ag + ions within an optimum range. Ag + ions deposit onto the Au surface through under potential deposition and facilitate the deposition of Pt through either direction to preferential sites, or by galvanic replacement.…”
Section: Seed-mediated Morphologymentioning
confidence: 98%
“…Upon varying the amount of Pt precursors, it was found that the synthesized Au@Pt CCB NCs with high Pt loading displayed better activities for the ORR with higher onset potentials (Figure 2A), furthermore, the highest Pt-loading materials displayed better stability than commercial Pt/C after 5,000 cycles of accelerated stress test (shifts of 28 and 39 mV respectively). (Roy et al, 2021).…”
Section: Seed-mediated Morphologymentioning
confidence: 99%